Impact of Full Periodic Call Auction on Stock Volatility and Liquidity in Watchlist Board of Indonesia Stock Exchange - Maria Christina Pasaribu; Buddi Wibowo (Eduvest - Journal of Universal Studies, 2025)
Indonesia Stock Exchange (IDX) has implemented a Full Periodic Call Auction (FCA) mechanism for stocks listed under the Watchlist Board on March 25, 2024 to enhance market quality and investor protection. This study investigates the impact of FCA mechanism on stock volatility and liquidity in the Indonesian capital market, particularly for equities listed on the Watchlist Board of IDX. Using a time-series regression framework and robust event study design, this research analyzes 40 stocks over a 12-month period surrounding the implementation of FCA on March 25, 2024. Volatility is measured using the Parkinson Volatility model, while liquidity is assessed using the Amihud Illiquidity Ratio. The results reveal that 80% of the sample experienced statistically significant changes in volatility, with 81.4% showing increased volatility, especially among low-priced stocks (< IDR 51). This supports the Thin Market Hypothesis and Market Microstructure Theory, suggesting that auction mechanisms can amplify price reactions in illiquid environments. Meanwhile, 55% of stocks showed significant changes in illiquidity, with 95.5% experiencing increased illiquidity, indicating that FCA may have inadvertently reduced market efficiency by limiting order flexibility and increasing execution risk under a blind order book. Aggregate testing confirms that FCA significantly increased volatility and weakened liquidity across the sample. These findings indicate that while FCA reactivated previously dormant stocks and facilitated price discovery in certain contexts, its effects are not uniformly beneficial. The outcomes vary depending on stock classification, with distress-level (Criteria 5) stocks showing volatility suppression, and low-price, low-liquidity stocks (Criteria 1) facing heightened trading frictions.